More Educated Sex Workers Earn More in Indonesia. Issue 3 (3rd July 2019) - Sohn, Kitae
ABSTRACT: Although sex work is prevalent, little is known about the relation between education and the price of sex. This study analyzed a dataset of 8, 817 Indonesian sex workers (SWs) to conduct an econometric analysis of the relationship between education and the price of sex. When the study controlled for demographic variables, an additional year of schooling was related to a 10 percent increase in the price. About half of this relation was explained by the location of sex, implying that education provided SWs with access to higher-paying clients via locations. The study also analyzed data on comparable non-SWs and found that the relation between education and the price of sex for SWs was the same in size as that of education to hourly earnings for non-SWs. The findings are consistent with the growing body of research that highlights the beneficial effects of education on outcomes beyond the conventional labor market.